Application of gonadosomatic index (GSI) and fecundity in interpreting the reproductive periodicity of an endemic snow trout, Schizothorax plagiostomus from the hill streams of Kashmir Himalaya - Magloo, AADIL HUSSAIN; Farooz Ahmad Bhat; Tasaduq H. Shah; Ashwani Kumar; Bilal Ahmad Bhat; Asim Iqbal Bazaz; Haziq Qayoom Lone; Sauliheen Qadri; Mudasir Ahmad Shah (Journal of Indian Fisheries Association, 2023)
The objective of the present study is to describe the phases of gonadal development using gonadosomatic index (GSI) and determine the fecundity of Schizothorax plagiostomus in Kashmir Himalaya. A total of 360 specimens of Schizothorax plagiostomus were studied for estimation of GSI and 95 female gonads for estimation of fecundity. The total length of the specimen ranged from 115 mm to 450 mm with the corresponding weight being 20 gm and 502 gm respectively. Maximum (gonadosomatic index) GSI values was recorded in the spawning month i.e. May with peak values of 11.4 in males and 13.0 in females. The mean absolute fecundity value of 95 specimens was 10676 ± 557. The mean relative fecundity (number of ova/gram of body weight) was found to be 42.66 ± 1.83 with highest of 95.69 and minimum of 7.53